Kemukjizatan Al-Qur’an dalam Segi Kebaasaan - Syukraini Ahmad; Dzakiyyah Raihanah Fadhilah; Rega Kusnadi; Nurul Azizah Fhadilah (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
The Qur’an is the last sacred text sent down by Allah to the Prophet Muhammad (peace be upon him). It was dispatched as a follow-up and conclusion to the earlier texts. There are clear resemblances between the teachings and messages present in the Qur’an and those in previous holy texts. Furthermore, the Qur’an stands as the most significant and unparalleled miracle bestowed upon the Prophet Muhammad by Allah. It encompasses various miraculous features. Nonetheless, certain individuals, particularly non-believers, reject it as factual. They view the Qur’an as merely common discourse or a text produced by the Prophet Muhammad, lacking true importance or significance. Typically, the miracles of the Qur’an can be classified into various types, including its linguistic beauty, its scientific precision, its narratives of historical peoples, and others. This paper will examine the extraordinary characteristics of the Qur’an by analyzing its linguistic elements